Antarctic Geomorphological and Glaciological 1:250,000 map series. Mt. Murchison Quadrangle (northern Victoria Land). Explanatory notes. (with geomorphological map at the scale of 1:250.000) - BARONI, CARLO; SALVATORE, MARIA CRISTINA; FREZZOTTI M.; MENEGHEL M.; TABACCO I. E.; VITTUARI L.; BONDESAN A.; BIASINI A.; CIMBELLI A.; OROMBELLI G. (Annals of Glaciology, 2004)
Geomorphological and glaciological features are represented on a georeferenced satellite image mosaic of the Mt. Murchison quadrangle (73°-74° S, 162°-166°30' E) at the scale of 1:250,000. Landforms and deposits of glacial and periglacial environments, forms related to mass wasting, wind action, weathering, and geological structures are identified and mapped. The chronological sequence of landforms and deposits, morphography and lithology are also indicated. Glacier velocities (up to 180 m a-1) and ice front fluctuations (1964-1999) have been determined by analysis of aerial photography and satellite imagery. Airborne radar surveys reveal that the greatest ice thickness (ca 1500 m) is located at the grounding zone of Aviator Glacier. Up to 1000 metres of ice bury the subglacial relief of Deception Plateau, Hercules Névé and the Deep Freeze Range. Snow accumulation rates (average = 170 kg m-2a-1) exhibit an overall negative correlation with altitude and distance from the coast. The relationships among relict erosional landforms and volcanic activity provide chronological constraints for the palaeogeographic evolution of this sector of the Transantarctic Mountains.